2000
DOI: 10.1074/jbc.m005820200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Sulfur-regulated Oxygenative Alkylsulfatase from Pseudomonas putida S-313

Abstract: The atsK gene of Pseudomonas putida S-313 was required for growth with alkyl sulfate esters as sulfur source. The AtsK protein was overexpressed in Escherichia coli and purified to homogeneity. Sequence analysis revealed that AtsK was closely related to E. coli taurine dioxygenase (38% amino acid identity). The AtsK protein catalyzed the ␣-ketoglutarate-dependent cleavage of a range of alkyl sulfate esters, with chain lengths ranging from C 4 to C 12 , required oxygen and Fe 2؉ for activity and released succin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 40 publications
5
71
0
2
Order By: Relevance
“…SDS was biodegraded efficiently at concentrations below its CMC with a mineralization rate significantly higher than that observed in a micellar phase. It has been shown that several bacteria, especially from the genera Pseudomonas, are able to biodegrade SDS through desulfation and further assimilation (Thomas and White, 1989;Kahnert and Kertesz, 2000). The important decrease in biodegradation rate for SDS, at higher concentration (1.41 g l À1 ) than its CMC, is in agreement with the results obtained by other authors (Abboud et al, 2007).…”
Section: Biodegradation Of Pcl-surfactants By Bacteriasupporting
confidence: 82%
“…SDS was biodegraded efficiently at concentrations below its CMC with a mineralization rate significantly higher than that observed in a micellar phase. It has been shown that several bacteria, especially from the genera Pseudomonas, are able to biodegrade SDS through desulfation and further assimilation (Thomas and White, 1989;Kahnert and Kertesz, 2000). The important decrease in biodegradation rate for SDS, at higher concentration (1.41 g l À1 ) than its CMC, is in agreement with the results obtained by other authors (Abboud et al, 2007).…”
Section: Biodegradation Of Pcl-surfactants By Bacteriasupporting
confidence: 82%
“…This Escherichia coli protein is a member of a rapidly expanding enzyme superfamily that utilizes mononuclear Fe(II) active sites to catalyze a diverse range of chemical transformations, usually coupled to the oxidative decarboxylation of an ␣-keto acid (2)(3)(4). Other family members include enzymes that modify protein side chains (5,6), repair alkylation-damaged DNA (7), degrade compounds in the environment (8)(9)(10)(11), and synthesize antibiotics (12)(13)(14), plant metabolites (15,16), or other small molecules (17,18). Most representatives carry out specific hydroxylation reactions, but examples of enzymes catalyzing desaturations, ring closures, and ring expansion reactions have also been documented (19).…”
mentioning
confidence: 99%
“…The first reports of this phenomenon involved prolyl hydroxylase, the enzyme whose malfunction underlies scurvy (10 -12) in which the uncoupled turnover results in the metal becoming oxidized in an ascorbic acid-reversible manner (13). Similar ascorbate-reversible uncoupled reactions have been reported for several other enzymes in this family, and ascorbic acid is a widespread component in the buffers used to assay these enzymes to avoid rapid inactivation (1). Assuming that the same mechanism of cosubstrate oxidation occurs for the substrate-free complex as in the catalytic cycle, a highly reactive Fe(IV)ϭO-ferryl species would be formed concomitantly with ␣KG decarboxylation.…”
mentioning
confidence: 92%
“…A solution containing the mother liquor and 10 mM Fe(NH 4 ) 2 (SO 4 ) 2 ⅐6H 2 O was added stepwise to the crystals to a total Fe 2ϩ concentration of 2 mM. The crystals were incubated under anaerobic conditions for 36 h. The space group changed upon soaking from P2 1 2 1 2 1 to I2 1 2 1 2 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation